Health technology assessment: factors affecting the results - Kozhanova, I. N. (Kachestvennai͡a︡ klinicheskai͡a︡ praktika, 2021)
Purpose: to identify factors influencing the results of health technology assessment (HTA). Methods. This analysis is based on previously performed clinical (pharmaco-) economic studies in the Republic of Belarus. The primary data analysis methods for inclusion in this publication have been cost-of-illness analysis (COI). The studies were carried out from 2010 to 2021. All costs are presented in US dollars based on exchange rates at the time of execution. Ranges are presented as maximum and minimum values. Results. The analysis of the influence of the stage of the disease, the stage of medical care, the form of release for drugs, the age of the target population for the use of health technology, the source of information on the price of technology on the results of the procedure for assessing medical technology has been performed. Evaluation of the ratio of the results of COI for implementation the clinical protocol and capabilities of the healthcare system (stable angina pectoris, type 2 diabetes mellitus), as well as for a number of special health technologies (hemophilia A; post-stroke spasticity; mantle cell lymphoma; chronic lymphocytic leukemia; chronic myeloid leukemia; lung cancer). Conclusions. It can be concluded that there is a need for clear formulations of goals and objectives at the stage of formation of the study design, considering the influence of the position of the researcher, the source of costs, the selected population, form of release (for drugs) on the main clinical and economic indicators and on the subsequent interpretation of the results of HTA.